Specificities of the monetary transmission mechanism within the Bulgarian currency board framework: The first five years - Martin N. Pazardjiev; Aleksandar Z. Vasilev (Journal of Central Banking Theory and Practice, 2021)
This paper presents an overview of the channels of monetary transmission and their manifestation in Bulgaria - a country in a currency board arrangement - in the first five years after the introduction of the regime. The presence of such a mechanism of transmission requires some form of macroeconomic discretion. The latter is approximated here with dynamics in the single fiscal account present on the balance sheet of the currency board.
Keywords: E42; E52; 330; monetary transmission; currency board; Bulgaria